The prospects of the Baby Boomers: Methodological challenges in projecting the lives of an aging cohort - Christian Westermeier; Anika Rasner; Markus M. Grabka (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
In most industrialized countries, the work and family patterns of the baby boomers characterized by more heterogeneous working careers and less stable family lives set them apart from preceding cohorts. Thus, it is of crucial importance to understand how these different work and family lives are linked to the boomers' prospective material well-being as they retire. This paper presents a new and unique matching-based approach for the projection of the life courses of German baby boomers, called the LAW-Life Projection Model. Basis for the projection are data from 27 waves of the German Socio-Economic Panel linked with administrative pension records from the German Statutory Pension In-surance that cover lifecycle pension-relevant earnings. Unlike model-based micro simula-tions that age the data year by year our matching-based projection uses sequences from older birth cohorts to complete the life-courses of statistically similar baby boomers through to retirement. An advantage of this approach is to coherently project the work-life and family trajectories as well as lifecycle earnings. The authors present a benchmark anal-ysis to assess the validity and accuracy of the projection. For this purpose, they cut a signif-icant portion of already lived lives and test different combinations of matching algorithms and donor pool specifications to identify the combination that produces the best fit be-tween previously cut but observed and projected life-course information. Exploiting the advantages of the projected data, the authors compare the returns to education - measured in terms of pension entitlements - across cohorts. The results indicate that within cohorts, differences between individuals with low and high educational attainment increase over time for men and women in East and West Germany. East German boomer women with low educational attainment face the most substantial losses in pension entitlements that put them at a high risk of being poor as they retire.
Keywords: C53; H55; I24; 330; forecasting models; simulation methods; SOEP; baby boomers; education; public pensions; Lebensverlauf; Prognoseverfahren; Simulation; Familiensoziologie; Lebensstandard; Rentner; Deutschland